PELATIHAN SUMBER DAYA MANUSIA (SDM) DALAM PENINGKATAN MUTU LAYANAN DI RUMAH SAKIT UMUM GRANMED LUBUK PAKAM - Linda Margata; Hariati Hariati; Jhan Saberlan (INSTITUT KESEHATAN DELI HUSADA, 2021)
The hospital is a service organization that has a variety in terms of human resources, infrastructure and equipment used. Hospital human resources are hospital assets that are very valuable because human resources control all activities in the hospital. Human resource development is a lifelong process, therefore it is related to adult education and lifelong learning. This development is also a process of helping and sharing that leads to competence and satisfaction with both the process and the outcome. Human Resource Development (HR) is one of the important factors that affect performance. The importance of human resources needs to be realized by all levels of management because of the advancement of technology today, the human factor still plays an important role for the success of an organization. The performance quality of human resources (HR) is a measure of the success of health services that can demonstrate the accountability of service institutions within the framework of good clinical governance. This training is aimed at developing human resources which is carried out to increase knowledge and skills related to the quality of hospital services.